2011
DOI: 10.3733/ucanr.7236
|View full text |Cite
|
Sign up to set email alerts
|

Cilantro Production in California

Abstract: Cilantro (Coriandrum sativium), also known as Mexican parsley, Chinese parsley, and coriander, is grown primarily along the southern and central coast of California. Ventura, Monterey, Santa Barbara, and San Benito Counties have the largest production, while smaller areas of production are scattered around the state. In the coastal counties production is year-round, with the main harvest from March through mid-November. Growers in the Coachella Valley (Riverside County) and the San Joaquin Valley plant a winte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…The 15.4% reduction in productivity may have been due to the initial development of the coriander plants having been slower under drip irrigation. This result is supported by Smith et al (2011), who recommend sprinkler irrigation during the initial phase of coriander production in order to improve germination and the establishing of the plants.…”
Section: Resultssupporting
confidence: 66%
“…The 15.4% reduction in productivity may have been due to the initial development of the coriander plants having been slower under drip irrigation. This result is supported by Smith et al (2011), who recommend sprinkler irrigation during the initial phase of coriander production in order to improve germination and the establishing of the plants.…”
Section: Resultssupporting
confidence: 66%
“…Since the primary symptoms observed in CYBD-affected cilantro plants in this study were similar to those described for cilantro yellow blotch disease in California (Koike et al 2007;Mayhew 2002;Smith et al 2011), it is conceivable that the California case may also be associated with similar mixed virus infection combinations. Hopefully, this report will stimulate further studies to revisit the etiology of the disease-affected cilantro plants in California.…”
supporting
confidence: 81%
“…Disease incidence at harvest time was estimated at~20% and the affected plants were rendered unmarketable. Due to the symptom resemblance to the California case (Koike et al 2007;Mayhew 2002;Smith et al 2011), we hypothesized that the observed disease in Texas was also likely to be of viral etiology. The goal of this study was to identify the putative etiological agents of CYBD.…”
mentioning
confidence: 99%
See 2 more Smart Citations